Antioxidant activity and total phenolic content of gamat water / Zaiton Mohamed Fauzi @ Jazuli - Mohamed Fauzi @ Jazuli, Zaiton (Faculty of Applied Sciences, 2010)
The antioxidant activity of gamat water were studied by using different assay that was total phenolic content (TPC) and 1,1-diphenyl-2-picryl hydrazyl (DPPH) method. The reading was measured using UV-VIS spectroscopy. The result show that, gamat water contain 0.0825 ± 0.0482 mg GAE/g total phenol and 16.8784% (at 3000ppm) in scavenging of DPPH radical. Gamat water contains less phenolic content and lower scavenging activity than standard gallic acid and ascorbic acid. This study, therefore, revealed that gamat water are potential sources of natural antioxidant other than can cure ailments.